Identification the internal parameters for mono-crystalline solar module using Matlab-simulation and experimental ascertainment - Rabea Q. Nafil; Hussein Thary Khamees; Munaf S. Majeed (Universitas Ahmad Dahlan, 2021)
The research studies the effects of some weather parameters for Baghdad city on the output of the solar module of the type monocrystalline. The experimental part measures the electrical parameters of the photo-voltaic (PV) module for three levels of radiation rate 500, 750, and 1000 W/m2. The theoretical part includes the modeled and simulation of the PV panel, via the proposed mathematical single–diode model (SDM, 5 parameters), and Matlab-simulation. The Newton Raphson method was applied to find the output current of the solar panel and the plotting P-V, I-V curves. The work involves preparing a simple mathematical model to estimate the optimal ambient conditions to give the highest output of the solar module. The validation of the model was verified by the practical testing of the cell for 6 months. The best results were obtained at standard testing conditions (25℃, 1000 W/m2). The output power calculated by the mathematical model was 30.1 W while from experimental work was 30.45 W. The relative error is 1.15%. The converge between experimental and modeling results for the same conditions is about 98.9% that proves the validity of the proposed model and the possibility of using it for all types of photovoltaic.